Frequency of mental disorders among chronic pain patients with or without fibromyalgia in Japan - Kenji Miki; Aya Nakae; Kenrin Shi; Yuka Yasuda; Hidenaga Yamamori; Michiko Fujimoto; Manabu Ikeda; Masahiko Shibata; Masao Yukioka; Ryota Hashimoto (Wiley, 2018)
Abstract Aim To explore the characteristics of psychiatric morbidity in chronic pain patients who present with or without fibromyalgia. Methods Patients are referred to our chronic pain clinic from primary medical institutions, as we are a secondary medical institution. Although some patients have chronic pain, they have no clear organic disorder such as rheumatoid arthritis to account for the pain. Among the 367 new patients seen during the period from March 2009 to August 2012, 347 patients underwent psychiatric evaluation in face‐to‐face interviews with mental health specialists before a physical examination. Results Of the 347 patients examined, at least one psychiatric diagnosis was made for 94.6%. The average number of DSM‐IV‐TR diagnoses was 1.46 in the 330 chronic pain patients who had at least one psychiatric diagnosis. The breakdown of the number of psychodiagnoses was one in 60.8%, two in 27.1%, three in 4.9%, and more than three in 2.3% chronic pain patients with or without fibromyalgia. In fibromyalgia patients, the highest relative frequencies were found for somatoform disorders (76%), followed by dysthymic disorder (17%) and major depressive disorder (15%). In patients without fibromyalgia, the highest relative frequencies were found for somatoform disorders (64%), followed by major depressive disorder (15%) and dysthymic disorder (14%). Psychiatric disorders were found in 96.9% of fibromyalgia patients, and in 93.5% of chronic pain patients without fibromyalgia in Japan (no significant difference using chi‐square test). Conclusion Results show that chronic pain patients with or without fibromyalgia are extremely likely to be diagnosed with a psychiatric disorder.